The Effectiveness of the SATUSIK Application to Improve Learning Motivation and Mastery of the Concept of Junior High School Digestive System Material - Nuryanti, Novi; Marianti, Aditya; Christijanti, Wulan (Universitas Negeri Semarang, 2024)
Learning media plays a very important role in the learning process, especially in the digital era. Students are used to using technology in their daily activities, so it is necessary to get used to using technology as well as in learning. Based on the results of initial observations conducted in 5 schools, it is known that the motivation to learn and mastery of the concept of grade VIII students is still relatively low, so learning media that can train these skills to students is needed. The purpose of this research is to analysis the effectiveness of SATUSIK Application to increase students’ motivation to learn and master concepts. The test subjects in this study are students of grade VIII MTs Darul Ulum Semarang and SMP N 2 Tengaran for the 2023/2024 academic year. The data analysis techniques used include analysis of learning motivation and concept mastery using the N-gain test. The mastery of the concept is also determined by the success of students in achieving scores above the Minimum Completeness Criteria (KKM). The results of the study showed that the effectiveness of the SATUSIK Application on students’ learning motivation was seen from the N-gain score of 0.84 with high criteria. The effectiveness of the SATUSIK Application on the mastery of concepts was seen from 86% of students were able to pass the KKM and after being tested N-gain got a score of 0.72 with a high category.